Rigid corrugated baffle system for tube-wave suppression in deep boreholes - Greenwood, Andrew; Dupuis, Christian; Abdulal, H.; Kepic, Anton (SEG, 2012)
Tube-waves are coherent waves which travel along the borehole/fluid interface of a fluid filled borehole. They are generated by the passage of an elastic wave exciting particle motion in the water column. These guided waves are the principal impediment to the use of hydrophones for routine VSP imaging as they mask the reflections needed to map seismic interfaces. Rigid corrugated baffles for tube-wave suppression have been tested in a laboratory experiment and in the field. Field experiments trialed 50 and 100 mm diameter polyethylene corrugated Agricultural drainage pipes (Ag pipe) as baffles. A number of permutations in the arrangement of the corrugated pipe were trialed to determine the effects of the diameter of the baffle and its overall length. We found that the corrugation of the Ag pipe successfully disrupted tube-wave propagation when the diameter of the baffle occupied a significant portion of the bore (66%). The most effective suppression was observed for a co-centric baffle arrangement where the 50 mm baffle was placed inside of the 100 mm baffle. The smaller diameter baffle (50 mm) by itself did not significantly affect the propagation of the tube-wave within a 125 mm diameter borehole whilst the larger diameter baffle on its own suppressed the Rayleigh generated tube-wave.